32/C would be the answer-
Answer:
![\left[\begin{array}{ccc}-25&\dfrac{75}{2}&-\dfrac{25}{2}\end{array}\right]](https://tex.z-dn.net/?f=%5Cleft%5B%5Cbegin%7Barray%7D%7Bccc%7D-25%26%5Cdfrac%7B75%7D%7B2%7D%26-%5Cdfrac%7B25%7D%7B2%7D%5Cend%7Barray%7D%5Cright%5D)
Step-by-step explanation:
In the first equality
![5\times \left[\begin{array}{cc}-1&2\\4&8\end{array}\right] =\dfrac{2}{5}m\times \left[\begin{array}{cc}-1&2\\4&8\end{array}\right],](https://tex.z-dn.net/?f=5%5Ctimes%20%5Cleft%5B%5Cbegin%7Barray%7D%7Bcc%7D-1%262%5C%5C4%268%5Cend%7Barray%7D%5Cright%5D%20%3D%5Cdfrac%7B2%7D%7B5%7Dm%5Ctimes%20%5Cleft%5B%5Cbegin%7Barray%7D%7Bcc%7D-1%262%5C%5C4%268%5Cend%7Barray%7D%5Cright%5D%2C)
the matrices in both parts are the saem. The equality will be true if the same matrices are multiplied by the same numbers, so
![5=\dfrac{2}{5}m\Rightarrow m=5\times \dfrac{5}{2}=\dfrac{25}{2}](https://tex.z-dn.net/?f=5%3D%5Cdfrac%7B2%7D%7B5%7Dm%5CRightarrow%20m%3D5%5Ctimes%20%5Cdfrac%7B5%7D%7B2%7D%3D%5Cdfrac%7B25%7D%7B2%7D)
For the second equality
![(H+[1\ 4\ -2])+[3\ 2\ -6]=[-2\ 3\ -1]+([1\ 4\ -2]+[3\ 2\ -6]),](https://tex.z-dn.net/?f=%28H%2B%5B1%5C%204%5C%20-2%5D%29%2B%5B3%5C%202%5C%20-6%5D%3D%5B-2%5C%203%5C%20-1%5D%2B%28%5B1%5C%204%5C%20-2%5D%2B%5B3%5C%202%5C%20-6%5D%29%2C)
if
, then this equality represents the assotiative property of matrix addition.
Hence,
![m\times H=\dfrac{25}{2}\times [-2\ 3\ -1]=\left[\begin{array}{ccc}-25&\dfrac{75}{2}&-\dfrac{25}{2}\end{array}\right]](https://tex.z-dn.net/?f=m%5Ctimes%20H%3D%5Cdfrac%7B25%7D%7B2%7D%5Ctimes%20%5B-2%5C%203%5C%20-1%5D%3D%5Cleft%5B%5Cbegin%7Barray%7D%7Bccc%7D-25%26%5Cdfrac%7B75%7D%7B2%7D%26-%5Cdfrac%7B25%7D%7B2%7D%5Cend%7Barray%7D%5Cright%5D)
Answer:
271
Step-by-step explanation:
1-4-6+56=47
47*6=282
282-8-3
271